2019
DOI: 10.1175/jcli-d-18-0330.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Abrupt 4 × CO2 Scenario to Elucidate Tropical Expansion Mechanisms

Abstract: Future emissions of greenhouse gases into the atmosphere are projected to result in significant circulation changes. One of the most important changes is the widening of the tropical belt, which has great societal impacts. Several mechanisms (changes in surface temperature, eddy phase speed, tropopause height, and static stability) have been proposed to explain this widening. However, the coupling between these mechanisms has precluded elucidating their relative importance. Here, the abrupt quadrupled-CO 2 sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
82
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(92 citation statements)
references
References 71 publications
(126 reference statements)
10
82
0
Order By: Relevance
“…It is suggested that this is due to the differing sensitivities of the HC edge and STJ strength to shifts in latitude of the peak eddy momentum flux, which would be consistent with previous work showing the HC edge's response to increased CO 2 is closely connected to changes in the midlatitudes (Chemke & Polvani, 2019;Shaw & Tan, 2018), while the STJ is more influenced by the tropics (Shaw & Tan, 2018). We examine both the natural variability and forced response of the HC and STJ in a large number of climate models and investigate the mechanisms causing variability and trends in the two features.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…It is suggested that this is due to the differing sensitivities of the HC edge and STJ strength to shifts in latitude of the peak eddy momentum flux, which would be consistent with previous work showing the HC edge's response to increased CO 2 is closely connected to changes in the midlatitudes (Chemke & Polvani, 2019;Shaw & Tan, 2018), while the STJ is more influenced by the tropics (Shaw & Tan, 2018). We examine both the natural variability and forced response of the HC and STJ in a large number of climate models and investigate the mechanisms causing variability and trends in the two features.…”
Section: Introductionsupporting
confidence: 87%
“…Interestingly, the shift of the HC and strengthening of the STJ occur on different time scales. For comparison, the global mean surface temperature increases even more slowly, taking around 65 years to reach 90% of its value at 150 years (Chemke & Polvani, 2019;Grise & Polvani, 2017;Seviour et al, 2018). The HC edge responds in 7 years, while the STJ does so in 40 years.…”
Section: Forced Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand why the Northern Hemisphere might be less responsive to the same SST forcing, we compute the changes in the vertical static stability ( C st ) for each hemisphere and season. In the Southern Hemisphere, it is well established that changes in subtropical static stability are closely connected with the expansion of the Hadley cell (Chemke & Polvani, ; Lu et al, ). The relationship between static stability and Hadley cell extent in the Northern Hemisphere in comprehensive models has been less explored, but it has generally been found that the statistical connections are weaker (e.g., cf.…”
Section: Resultsmentioning
confidence: 99%
“…Given the significant effect of Arctic sea ice loss on φ Ψ500 , we next seek to elucidate the mechanisms. Held () developed a theory for the HC width, which is able to explain the projected widening of the HC (e.g., Chemke & Polvani, ). In that theory, the edge of the HC (φ H00 ) is determined by the latitude where the vertical shear of the mean angular momentum conserving flow at the upper branch of the HC becomes baroclinically unstable and scales as follows: ϕnormalH00()NHenormalΩa1false/2, where H e is subtropical tropopause height, N2=gθθz is subtropical static stability (averaged between 400 and 800 mb), and Ω is Earth's rotation rate.…”
Section: Resultsmentioning
confidence: 99%